Intradialytic Hypotension During Heamodyalysis - Rehman, Zia Ur; Noor Mohammad; Khan, Muhammad Waqas; Muhammad, Shad; Khan, Muhammad Umair; Khan, Tahir Ullah; Akhunzada, Mohammad Ikram (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES Haemodialysis (HD) is a form of renal replacement therapy commonly prescribed for chronic kidney disease (CKD) patients. However, it is not without deleterious haemodynamic responses which may occur either during or immediately after the termination of the procedure. These may include hypotension or hypertension. The objective of this study was to determine the frequency of intradialytic blood pressure changes in chronic kidney disease patients on maintenance hemodialysis. METHODOLOGY Patients with chronic kidney disease on maintenance hemodialysis were enrolled. Predialysis and immediate post dialysis blood pressure was recorded. Increase in postdialysis blood pressure by >20mmHg was called intradialytic hypertension and decrease by >20mmHg was called intradialytic hypotension. RESULTS A total of 203 patients on maintenance hemodialysis were enrolled. Age of the patients ranged from 18 to 50 years. Mean age of the patients was 39.80 ± 5.245 years. Male to female ratio was 1.8:1. Intradialytic hypotension was observed in 36 patients (17.7%) while intradialytic hypertension was observed in 22 patients (10.8%). CONCLUSION Intradialysis blood pressure fluctuations such as hypotension and hypertension are common complications during hemodialysis. Intradialytic hypotension is more frequent.